2022
DOI: 10.1038/s41598-022-22966-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genomic heritability and genome-wide association studies for blood parameters in Akkaraman sheep

Abstract: The aim of this study was to estimate genomic heritability and the impact that genetic backgrounds have on blood parameters in Akkaraman sheep by conducting genome-wide association studies and regional heritability mapping analysis. Genomic heritability estimates for blood parameters ranged from 0.00 to 0.55, indicating that measured phenotypes have a low to moderate heritability. A total of 7 genome- and 13 chromosome-wide significant SNPs were associated with phenotypic changes in 15 blood parameters tested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…At 18 months of age, approximately 78 of these female animals had a second fleece sampling, which was additionally weighed for greasy fleece (an example of Akkaraman wool presented as Supplementary Figure S2 ). Further information on the climatic and geographic conditions of the region, herd management, mating, selection strategy and feeding practices were presented in detail previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 18 months of age, approximately 78 of these female animals had a second fleece sampling, which was additionally weighed for greasy fleece (an example of Akkaraman wool presented as Supplementary Figure S2 ). Further information on the climatic and geographic conditions of the region, herd management, mating, selection strategy and feeding practices were presented in detail previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Reference genomes have been published for domestic sheep and high density commercial arrays have been developed for genome-wide distributed single nucleotide polymorphisms (SNPs), which can be employed to map the relationship between economically important traits and genomic loci [ 19 ]. Genomic data have been used effectively in many studies to discover SNPs, major variants, genes and quantitative trait loci (QTLs) associated with traits in farm animals [ 20 , 21 , 22 , 23 , 24 , 25 ]. The information obtained from these studies can be incorporated into systematic breeding programmes to achieve rapid genetic improvement of the studied traits [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 45% of domestic sheep in Türkiye are Akkaraman ( Ozmen et al, 2020 ). They are known for their adaptability to arid environments, cold resilience, disease resistance or tolerance, and ability to thrive on low-quality pastures ( Arzik et al, 2022a ). The Karakas in Eastern Anatolia, Kangal in Central Anatolia, Savak in Eastern Anatolia, Guney Karaman in the Mediterranean, and Norduz in the Eastern Anatolian regions are recognized as varieties/subtypes of the Akkaraman ( Ozmen et al, 2020 ).…”
Section: Sheep Breeds In Türkiyementioning
confidence: 99%
“…Since both the number of goats and the number of other domestic breeds are not competitive compared to the world-wide breeds in terms of production, their numbers are decreasing day by day. Although studies have been carried out to identify the genetic potential of domestic animal genetic resources in terms of economically important traits, these studies are not yet sufficient in Türkiye (Gül et al, 2020;Behrem, 2021;Kizilaslan et al, 2022;Arzik et al, 2022;Yilmaz et al, 2022). There are similar situations in Angora goats, and unfortunately their number has experienced a serious decline for a period.…”
Section: Introductionmentioning
confidence: 99%